Interstitial macrophage-derived thrombospondin-1 contributes to hypoxia-induced pulmonary hypertension. Issue 12 (9th November 2019) - Kumar, Rahul; Mickael, Claudia; Kassa, Biruk; Sanders, Linda; Hernandez-Saavedra, Daniel; Koyanagi, Daniel E; Kumar, Sushil; Pugliese, Steve C; Thomas, Stacey; McClendon, Jazalle; Maloney, James P; Janssen, William J; et al.
Abstract: Aims: Transforming growth factor-β (TGF-β) signalling is required for chronic hypoxia-induced pulmonary hypertension (PH). The activation of TGF-β by thrombospondin-1 (TSP-1) contributes to the pathogenesis of hypoxia-induced PH. However, neither the cellular source of pathologic TSP-1 nor the downstream signalling pathway that link activated TGF-β to PH have been determined. In this study, we hypothesized that circulating monocytes, which are recruited to become interstitial macrophages (IMs), are the major source of TSP-1 in hypoxia-exposed mice, and TSP-1 activates TGF-β with increased Rho-kinase signalling, causing vasoconstriction. Methods and results: Flow cytometry revealed that a specific subset of IMs is the major source of pathologic TSP-1 in hypoxia. Intravenous depletion and parabiosis experiments demonstrated that these cells are circulating prior to recruitment into the interstitium. Rho-kinase-mediated vasoconstriction was a major downstream target of active TGF-β. Thbs1 deficient bone marrow (BM) protected against hypoxic-PH by blocking TGF-β activation and Rho-kinase-mediated vasoconstriction. Conclusion: In hypoxia-challenged mice, BM derived and circulating monocytes are recruited to become IMs which express TSP-1, resulting in TGF-β activation and Rho-kinase-mediated vasoconstriction. Graphical Abstract: